Micro-Learning Keagamaan di Media Sosial: Tantangan Kedalaman Materi dalam Pendidikan Agama Islam Digital - Supriadi; Miftahur Rizik; Nur Achmadi; Muhammad Munif; Mona Novita (IEC: Journal of Educational Innovation, 2026)
The rapid expansion of social media has transformed the landscape of informal religious learning, making short-form religious microlearning increasingly accessible to Muslim digital audiences. While existing studies have widely emphasized the communicative reach, accessibility, and engagement potential of digital religious content, limited attention has been given to its pedagogical adequacy within the framework of Islamic Religious Education. This study examines the extent to which short-form religious microlearning content on social media provides sufficient pedagogical depth to support meaningful Islamic learning. Using a qualitative evaluative content analysis design, this study analyzed 180 publicly accessible short-form Islamic religious videos on TikTok, selected through purposive sampling from content published between January and June 2026. Data were evaluated using the Pedagogical Depth Deficit Framework developed in this study, integrating microlearning theory, deep learning pedagogy, and Islamic Religious Education perspectives. The analysis focused on conceptual depth, contextual integrity, scriptural integrity, reflective potential, ethical complexity, dialogic openness, and overall pedagogical sufficiency. The findings indicate that while religious microlearning demonstrates strong accessibility and rapid message delivery, most content exhibits limited pedagogical depth, particularly in conceptual elaboration, reflective engagement, contextual explanation, and dialogic openness. These patterns suggest that short-form religious content functions more effectively as religious informational exposure than as substantive Islamic learning. This study contributes conceptually by introducing the notions of pedagogical compression and pedagogical depth deficit as analytical lenses for evaluating digital religious learning. Practically, the findings underscore the need for more pedagogically responsible design in digital Islamic education, particularly when integrating social media-based microlearning into Islamic Religious Education contexts.